The Urgency of Budget Independence for the Constitutional Court in Strengthening the Independence of the Judiciary - Adam Ilyas; Paulus Rudy Calvin Sinaga (Indonesian Journal of Administrative Law and Local Government, 2024)
This study analyzes the importance of budgetary independence for Indonesia’s Constitutional Court (Mahkamah Konstitusi or MK) to strengthen its independence as a judicial institution. Budgetary independence is deemed essential for MK to perform its functions without political pressure or intervention from the executive and legislative branches. This research employs a normative legal method with a descriptive-analytical approach to examine relevant regulations, legal literature, and international practices related to budgetary independence for constitutional courts. The results show that budgetary independence plays a significant role in enhancing operational flexibility, safeguarding institutional autonomy, and strengthening MK’s credibility in the public eye. With an independent budget, MK can allocate resources according to its needs without political influence. This study also provides strategic recommendations, such as the formulation of specific policies, the establishment of an independent oversight body, a special budget model, and capacity-building for MK’s financial management. These recommendations are expected to support a more independent and accountable judicial system. Budgetary independence will enable MK to perform its duties effectively and uphold its integrity as a neutral guardian of the constitution.